The Relationship Between Knowledge and Attitude of Midwives with Infection Prevention and Control Practices in Mempawah Regency, West Kalimantan, Indonesia - Yulianti; Febry Mutiariami Dahlan; Putri Azzahroh (Rajaki of Tulip Medika Publisher, 2026)
Particularly in primary healthcare settings, healthcare-associated infections (HAIs) continue to be considered a serious threat to maternal and neonatal care. In order to lower the risk of infection, midwives are critical for the implementation of Infection Prevention and Control (IPC) strategies. However, midwives' adherence to IPC procedures is frequently inconsistent and might be impacted by personal characteristics like attitude and knowledge.The purpose of this study proved to determine how midwives' attitudes and knowledge related to infection prevention and control (IPC) practices in Mempawah Regency, West Kalimantan, Indonesia. Midwives employed by Mempawah Regency's district health office and primary healthcare facilities participated in a quantitative cross-sectional study. Purposive sampling was used to identify 76 midwives within total. A validated and structured questionnaire measuring IPC practices, knowledge, and attitude was used to collect data. The Chi-square test was used to analyze the data at a significance level of p < 0.05. It was found that midwives who had positive attitudes and good knowledge were more likely to apply IPC practices correctly. A statistically significant correlation (p < 0.05) was found between knowledge and IPC practices, as well as between attitude and IPC practices. Midwives' infection prevention and control practices have a significant correlation with their knowledge and attitudes. To enhance IPC implementation in primary healthcare settings, encouragement and ongoing training must be strengthened.